PERENCANAAN STRATEGIS SISTEM INFORMASI PADA INDUSTRI SUKU CADANG OTOMOTIF MENGGUNAKAN METODE WARD DAN PEPPARD (STUDI KASUS PT XYZ) - Maulidiyah, Ratna; Putri, Tansa Trisna Astono (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2020)
The automotive industry is required to carry out product development and distribution of production results in accordance with market needs. PT XYZ is the largest and leading automotive group company in Indonesia that manufactures and distributes a wide range of two-wheeled and four-wheeled motor vehicle parts. The growth of national economy that relatively low affects on the weakening of the purchasing power of the people, thereby contributing negatively to the growth of the spare-parts market. In addition, there are several strategic issues that have occurred at PT XYZ. Based on these strategic issues, an information system strategic planning is needed, with the aim of supporting the course of the company's business processes and supporting the application of information systems and IT infrastructure that follows the development of business and technology. This research covers business models, analysis of the business environment, issues that arise from information systems strategies, and the preparation of IS, IT, and IS/IT management strategies. This study uses a model from Ward and Peppard. The stages carried out in this study are analysis of current conditions, analysis of future conditions, gap analysis and strategic planning, as well as the preparation of a roadmap and migration plan. The outputs of this study are twelve information systems development, five IT infrastructure developments, and three IS/IT management developments.